Evaluasi Stabilitas Lereng Situs Ratu Boko Berdasarkan Simulasi Numeris - , UMRAN SARITA, Dr. Ir. Ahmad Rifaâi, M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Ratu Boko Site is a historical site that might be protected its existence in Sleman regency, DI Yogyakarta province. The building of supported facilities of the Ratu Boko site caused the geometrical change and olso slope loading. Yogyakarta earthquake 2006, ocoured instability of the Plaza Andrawina building, such as beam and column crack, whereas it has carried out the rehabilitation with supported column. Research observation are slope deformation, safety factor, coused of building instability and the effectivity of rehabilitation. In this study, the analysis using finite element method with the plan strain model by the assistance of Plaxis V8.2 software. The model that is used are natural slope, after the slope change and building facilities and after rehabilitation as well. The geometry input and layer structure from topography data and field observation. While the soil parameter input, rock and concrete from secondary data which is validated before. The analysis model is static and dynamic load. In regard of numerical simulation, occurred the deformation after the change of geometrical slope of the Ratu Boko site. The consequence of building facilities, occurred increasing of deformation either static load or dynamic load around outside foundation. By viewing from slope stability, also occurred the decrease of slope safety factor up to this condition is 1,274 compared with natural slope is 2,767, and olso the increasing displacement different to both outside foundation that is induced space of both columns changed such as existing condition by + 3 cm. the crack of joined beam and column outside such as existing condition (1-2mm) effected by the accumulation of outside vertical foundation displacement more than after the earthquake and excavation foundation so that it induced angular distortion is 1/213. After setting out the supported column it is effective enough to reduce the increasing before, by caused of earthquake load the difference of displacement within both outside column is 1mm, the displacement of inside vertical foundation more than of outside foundation with the result that it reduces angular distortion before becoming 1/148, as well as increasing the safety factor of slope when the earthquake that is 2,489. In terms of angular distortion, due to static load the values obtained still relatively high that is 1/199 if supported column carried out together with building facilities, but this damage including light.numerical approach 2D model with software Plaxis proved to be able to model of soil structure as well as building altogether to obtain their interaction.